Implementation of sharia principles in the insurance industry in Indonesia: Systematic Literature Review - Isnaini Hikmah Hidayah; Taufiqur Rahman (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - Aims to examine in depth the implementation of sharia principles in the insurance industry in Indonesia. The main focus is to evaluate the extent to which principles such as monotheism, justice, ta'awun, and cooperation are implemented through sharia contracts such as tabarru', tijarah, mudharabah musytarakah, and wakalah bil ujrah in sharia insurance practices. Method - The method used in this study is Systematic Literature Review (SLR). Data were collected from 500 articles filtered through Google Scholar with the keywords "sharia principles" and "insurance industry" in the period 2020-2025. After going through the selection and data cleaning stages, the seven most relevant articles were analyzed in depth to identify key findings and academic trends related to the topic. Result - The results of the study show that although sharia insurance has a strong basis in Islamic principles, its implementation still faces several major challenges. Among them are low public literacy, lack of standardization in the implementation of contracts, weak regulations from the government, and less than optimal services comparable to conventional insurance. In addition, there was a gap in understanding between industry players and customers regarding sharia contracts. Implication - emphasizes the need to strengthen education, improve service systems, and formulate regulations that are more supportive of the development of the sharia insurance industry. This study also recommends increasing the role of the Sharia Supervisory Board in ensuring operational compliance with sharia values. Originality - This study provides an original contribution through a systematic literature approach, by integrating various dimensions of sharia (theological, managerial, social, and digital) in its analysis. This study is expected to be a theoretical and practical reference for academics, regulators, and industry players in strengthening the sharia financial system in Indonesia. Keywords:                     Sharia insurance , Sharia principles, Insurance industry.